All-solid-state battery and method for producing same

The all-solid-state battery design with a lithium metal layer and pre-lithiated negative electrode active material layer addresses the challenge of increasing battery capacity, achieving improved Coulomb efficiency and discharge capacity.

JP2025507807APending Publication Date: 2025-03-21LG ENERGY SOLUTION LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024551600
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-11-10
Filing Date
2023-11-10
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing all-solid-state batteries face challenges in increasing battery capacity efficiently through the prelithiation step, which is crucial for enhancing Coulomb efficiency and overall battery performance.

Method used

The proposed solution involves an all-solid-state battery design where a lithium metal layer and a negative electrode active material layer are sequentially laminated, with the negative electrode active material layer being pre-lithiated. This design includes a specific structure and manufacturing process to optimize the ratio of initial charge capacities between the positive and negative electrodes, ensuring efficient prelithiation and improved battery capacity.

Benefits of technology

The described solution effectively increases the Coulomb efficiency of the negative electrode and enhances the battery capacity, as demonstrated by the increased discharge capacity in the experimental results compared to comparative examples.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025507807000001_ABST
    Figure 2025507807000001_ABST
Patent Text Reader

Abstract

The present invention relates to an all-solid-state battery and a manufacturing method thereof. More specifically, the present invention provides an all-solid-state battery in which a negative electrode, a solid electrolyte layer, and a positive electrode are sequentially stacked, and when a negative electrode active material layer containing a negative electrode active material capable of alloying with lithium or forming a compound with lithium is introduced into the negative electrode of the all-solid-state battery and the negative electrode is pre-lithiated, the Coulombic efficiency of the negative electrode is increased and the battery capacity is increased, and a manufacturing method thereof can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0149206 dated November 10, 2022 and Korean Patent Application No. 10-2023-0154969 dated November 10, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to an all-solid-state battery and a manufacturing method thereof. [Background technology]

[0003] Recently, interest in energy storage technology has been increasing. As the fields of application have expanded to include mobile phones, video cameras, and laptop computers, as well as the energy of electric vehicles, efforts in the research and development of electrochemical devices have become more and more concrete. Electrochemical devices are the field that has attracted the most attention in this regard, and among them, the development of secondary batteries that can be charged and discharged has become a focus of attention. Recently, in order to develop such batteries, research and development has been conducted on new electrode and battery designs to improve capacity density and specific energy.

[0004] Of the secondary batteries currently in use, lithium secondary batteries, developed in the early 1990s, have been attracting attention for their advantages of higher operating voltage and significantly greater energy density than conventional batteries that use aqueous electrolytes, such as Ni-MH, Ni-Cd, and sulfuric acid-lead batteries.

[0005] Such lithium secondary batteries have traditionally used liquid electrolytes (electrolytic solutions) such as flammable organic solvents, etc. However, batteries using liquid electrolytes can cause problems such as electrolyte leakage, fire, and explosion.

[0006] In order to solve these problems and ensure essential safety, active research is being conducted into the use of solid electrolytes instead of liquid electrolytes. All solid-state batteries, in which all components, including the electrolyte, are solid, are called all-solid-state batteries. All-solid-state batteries are attracting attention as the next generation of lithium secondary batteries from the standpoints of safety, high energy density, high output, and simplified manufacturing processes.

[0007] In order to increase the energy density and produce a high-power battery, such an all-solid-state battery can use lithium metal itself as the negative electrode, or can use the negative electrode current collector alone as the negative electrode without the negative electrode active material.

[0008] Generally, if the first cycle coulombic efficiency of the negative electrode is lower than that of the positive electrode, this can cause a decrease in battery capacity. However, pre-lithiation of the negative electrode increases the coulombic efficiency of the negative electrode, thereby increasing the battery capacity.

[0009] Therefore, there is a need for a method for simply and efficiently increasing the capacity of a battery through a pre-lithiation process that is applicable to all-solid-state batteries. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Korean Patent Publication No. 2020-0134126 [Patent Document 2] Korean Patent Publication No. 2020-0129383 Summary of the Invention [Problem to be solved by the invention]

[0011] As a result of extensive research to solve the above problems, the present inventors have found that when a negative electrode active material layer including a negative electrode active material capable of forming an alloy with lithium or a compound with lithium is introduced into a negative electrode of an all-solid-state battery in which a negative electrode, a solid electrolyte layer, and a positive electrode are sequentially stacked, and the negative electrode is pre-lithiated, the Coulombic efficiency of the negative electrode is increased and the battery capacity is increased.

[0012] Therefore, an object of the present invention is to provide an all-solid-state battery having increased capacity due to a pre-lithiation process and a method for producing the same. [Means for solving the problem]

[0013] In order to achieve the above object, the present invention provides an all-solid-state battery including a positive electrode, a negative electrode, and a solid electrolyte layer, wherein the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on one surface of the positive electrode current collector, the negative electrode includes a negative electrode current collector, a lithium metal layer formed on one surface of the negative electrode current collector, and a negative electrode active material layer formed on one surface of the lithium metal layer, the solid electrolyte layer is disposed between the positive electrode active material layer and the negative electrode active material layer, and the negative electrode active material layer includes a negative electrode active material capable of forming an alloy with lithium or forming a compound with lithium, and lithium.

[0014] The present invention also provides an all-solid-state battery, wherein in the negative electrode active material layer, the concentration of the lithium has a concentration gradient that gradually decreases from one surface in contact with the lithium metal layer to the other surface.

[0015] The present invention also provides an all-solid-state battery, in which the lithium contained in the negative electrode active material layer is diffused in the form of lithium ions or exists in a form bound to the negative electrode active material.

[0016] The present invention also provides an all-solid-state battery, wherein the negative electrode active material includes one or more selected from the group consisting of amorphous carbon, gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn).

[0017] The present invention also provides an all-solid-state battery, wherein the negative electrode active material layer has a thickness of 5 to 200 μm.

[0018] The present invention also provides an all-solid-state battery, wherein a ratio of an initial charge capacity of the positive electrode active material layer to an initial charge capacity of the negative electrode active material layer satisfies the following formula 1:

[0019] [Formula 1] 0 ≦ (b / a) < 0.01 Here, a is the initial charge capacity of the positive electrode active material layer determined from the first open circuit voltage to the maximum charge voltage (vs Li / Li+), b is the charge capacity of the negative electrode active material layer determined from the second open circuit voltage to 0.01 V (vs Li / Li+).

[0020] The present invention also provides (1) applying a slurry containing a negative electrode active material capable of alloying with lithium or forming a compound with lithium onto a negative electrode support and drying the slurry to form a negative electrode active material layer; (2) coating a slurry containing a positive electrode active material on a positive electrode current collector, drying the slurry, and then forming a positive electrode active material layer to manufacture a positive electrode; (3) disposing a solid electrolyte layer between the negative electrode active material layer and the positive electrode active material layer to form a laminate; (4) removing the negative electrode support from the laminate after pressing the laminate; (5) attaching a lithium thin film to one surface of the negative active material layer from which the negative support has been removed, and pre-lithiating the negative active material layer; (6) attaching a negative electrode current collector to the other side of the lithium thin film; and (7) A method for manufacturing an all-solid-state battery, comprising: pressurizing the battery manufactured in the step (6).

[0021] The present invention also provides a method for producing an all-solid-state battery, wherein the pressing in step (4) is isostatic pressing or uniaxial pressing under a pressure of 300 to 800 MPa and a temperature of 20 to 150°C.

[0022] The present invention also provides a method for producing an all-solid-state battery, wherein the pressurization in step (7) is followed by aging.

[0023] The present invention also provides a method for producing an all-solid-state battery, wherein the pressing is isostatic pressing or uniaxial pressing at a pressure of 0.05 to 100 MPa.

[0024] The present invention also provides a method for producing an all-solid-state battery, wherein the aging is performed by storing the battery at a temperature of 20 to 100°C. Effect of the Invention

[0025] The negative electrode of the all-solid-state battery according to the present invention has a structure in which a negative electrode current collector, a lithium metal layer, and a negative electrode active material layer are sequentially stacked, and during the manufacturing process, the negative electrode active material layer is prelithiated by the adjacent lithium metal layer, thereby increasing the Coulombic efficiency of the negative electrode and improving the capacity of the battery. [Brief description of the drawings]

[0026] [Figure 1] 1 is a schematic diagram showing a manufacturing process of an all-solid-state battery according to Example 1. FIG. [Diagram 2] 1 is a graph showing the initial charge / discharge profiles of all-solid-state batteries produced in Example 1 and Comparative Example 1, respectively. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] The present invention will now be described in further detail to aid in the understanding of the present invention.

[0028] The terms and words used in this specification and claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that corresponds to the technical idea of ​​the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his / her invention.

[0029] As used herein, the term "pre-lithiation" refers to a state in which lithium is diffused and / or intercalated between or combined with a material capable of absorbing and releasing lithium.

[0030] all solid state battery The present invention relates to an all-solid-state battery, the all-solid-state battery including a positive electrode, a negative electrode, and a solid electrolyte layer, the positive electrode including a positive electrode current collector and a positive electrode active material layer formed on one surface of the positive electrode current collector, the negative electrode including a negative electrode current collector, a lithium metal layer formed on one surface of the negative electrode current collector, and a negative electrode active material layer formed on one surface of the lithium metal layer, the solid electrolyte layer being disposed between the positive electrode active material layer and the negative electrode active material layer, the negative electrode active material layer including a negative electrode active material capable of forming an alloy with lithium or a compound with lithium, and lithium.

[0031] The negative electrode included in the all-solid-state battery according to an embodiment of the present invention includes a negative electrode current collector, a lithium metal layer formed on one surface of the negative electrode current collector, and a negative electrode active material layer formed on one surface of the lithium metal layer.

[0032] In one embodiment of the present invention, the negative electrode active material layer includes a negative electrode active material and lithium, and may further include one or more selected from a binder and a conductive material.

[0033] The negative electrode active material layer also functions as a protective layer for the lithium metal layer, and therefore can have an appropriate thickness to ensure the physicochemical properties required during cell operation. The thickness of the negative electrode active material layer may be 0.1 to 500 μm. Specifically, the thickness of the negative electrode active material layer may be 0.1 μm or more, 5 μm or more, 10 μm or more, 30 μm or more, 50 μm or more, or 100 μm or more, and may be 200 μm or less, 300 μm or less, 400 μm or less, or 500 μm or less. If the thickness of the negative electrode active material layer is less than 0.1 μm, the mechanical strength of the negative electrode active material layer may decrease, and if it exceeds 500 μm, the lithium ion transfer resistance may increase.

[0034] In the present invention, the negative electrode active material is not particularly limited as long as it is an anode active material that can be alloyed with lithium or form a compound with lithium. For example, the negative electrode active material may include one or more selected from the group consisting of amorphous carbon, gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn).

[0035] The negative electrode active material may be included in an amount of 50 to 99.9 wt % based on the total weight of the negative electrode active material layer.

[0036] The lithium may be introduced in a pre-lithiation process of the negative electrode active material layer during the manufacturing process of the all-solid-state battery.

[0037] The lithium may be partially contained within the negative electrode active material layer. The negative electrode active material layer may be in an anodeless state in which the amount of lithium that can enter without being deposited is less than the amount of lithium that can be released from the positive electrode. In general, an anodeless cell may be operated in such a way that the amount of lithium that can be released from the positive electrode is much greater than the amount of lithium that can enter the negative electrode, and lithium deposition occurs after the negative electrode is filled with lithium. Due to the first cycle irreversible capacity of the negative electrode active material, the first cycle efficiency of the cell may decrease as the negative electrode capacity increases, and thus the discharge capacity (reversible capacity) may decrease. Therefore, it may be preferable to include lithium within the negative electrode active material layer to reduce the first cycle charge capacity of the negative electrode active material excluding lithium deposition. The negative electrode active material layer is required to have a certain thickness since it also serves as a protective layer for the lithium metal layer. In order to include lithium in the negative electrode active material layer having a certain thickness, the negative electrode active material layer may be formed by performing a pre-lithiation process.

[0038] The lithium may be included in an amount of 0.1 wt% to 50 wt% based on the total weight of the negative electrode active material layer. Specifically, the lithium content may be 0.1 wt% or more, 3 wt% or more, 5 wt% or more, or 10 wt% or more, and 30 wt% or less, 40 wt% or less, or 50 wt% or less. If the lithium content is less than 0.1 wt%, the increase in the first cycle efficiency of the cell may be negligible, and if it exceeds 50 wt%, the first cycle coulombic efficiency of the negative electrode active material layer becomes greater than the first cycle coulombic efficiency of the positive electrode active material layer, so that the weight and volume of the battery are increased without increasing the reversible capacity of the cell, and the improvement effect may be reduced. At this time, the lithium content included in the negative electrode active material layer includes the lithium inserted into the negative electrode active material layer through the pre-lithiation process.

[0039] The pre-lithiation process may be performed by attaching a lithium thin film to one surface of the negative active material layer, and thus, the lithium introduced into the negative active material layer by the pre-lithiation process may exist while forming a concentration gradient that varies depending on the position within the negative active material layer.

[0040] In the negative active material layer, the lithium concentration may have a concentration gradient that gradually decreases from one surface in contact with the lithium metal layer to the other surface. In this case, the lithium metal concentration having a concentration gradient that gradually decreases may mean a continuous decrease and a discontinuous decrease in the lithium metal concentration.

[0041] The concentration gradient composition and concentration can be confirmed using a method such as an electron probe micro analyzer (EPMA), an inductively coupled plasma-atomic emission spectrometer (ICP-AES), a time of flight secondary ion mass spectrometry (ToF-SIMS), or X-ray photoelectron spectroscopy (XPS). Specifically, the atomic ratio of each metal can be measured by moving from the center to the surface of the negative electrode current collector using an EPMA, or the atomic ratio of each metal can be measured by etching the negative electrode current collector from the surface to the center using XPS.

[0042] In the present invention, the binder that can be included in the negative active material layer can improve the bond between the negative active material and the conductive material and the bond to the negative current collector. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers thereof.

[0043] The binder may be included in an amount of 1 wt% to 30 wt% based on the total weight of the negative electrode active material layer, and specifically, the binder content may be 1 wt% or more, 3 wt% or more, or 5 wt% or more, and 15 wt% or less, 20 wt% or less, 25 wt% or less, or 30 wt% or less. If the binder content is less than 1 wt%, the adhesive strength between the negative electrode active material and the lithium metal layer may be reduced, and if it exceeds 30 wt%, the adhesive strength is improved, but the lithium ion resistance may be increased, and cell performance may be reduced.

[0044] In the present invention, the conductive material that can be contained in the negative electrode active material layer can be used to further improve the conductivity of the negative electrode active material. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and can be, for example, graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black; conductive fiber such as carbon fiber or metal fiber; metal powder such as carbon fluoride, aluminum, nickel powder; conductive whisker such as zinc oxide, potassium titanate; conductive metal oxide such as titanium oxide; polyphenylene derivatives, etc.

[0045] The conductive material may be included in an amount of 0.5 to 30 wt % based on the total weight of the negative electrode active material layer. Specifically, the content of the conductive material may be 0.5 wt % or more, 1 wt % or more, or 3 wt % or more, and may be 10 wt % or less, 15 wt % or less, 20 wt % or less, 25 wt % or less, or 30 wt % or less. If the content of the conductive material is too low, such as less than 0.5 wt %, it may be difficult to expect an improvement in electrical conductivity or the electrochemical properties of the battery may be deteriorated, and if the content is too high, such as more than 30 wt %, the amount of the negative electrode active material may be relatively small, and the capacity and energy density may be reduced.

[0046] In one embodiment of the present invention, the lithium metal layer is introduced during the process of prelithiating the negative electrode active material layer, and the lithium metal layer may include lithium and / or a lithium alloy. The lithium and / or lithium alloy may also be used as the negative electrode active material.

[0047] The thickness of the lithium metal layer may be more than 0 μm, 1 μm or more, 3 μm or more, or 5 μm or more, or may be 10 μm or less, 15 μm or less, 20 μm or less, 25 μm or less, or 30 μm or less. When the thickness of the lithium metal layer is 0 μm, the capacity of lithium is smaller than the charge capacity of the negative electrode active material, so that all lithium in the lithium metal layer is used for prelithiation, which means that a lithium metal layer exists. When the thickness of the lithium metal layer is within the above range and the capacity of lithium is larger than the charge capacity of the negative electrode active material, a remaining lithium metal layer may exist. The thicker the lithium metal layer, the more the battery life can be extended by compensating for lithium consumed in side reactions occurring at the negative electrode, but when the thickness is excessively thick, such as 30 μm or more, the reduction in battery energy density is large relative to the effect of extending the life, which is not efficient.

[0048] In one embodiment of the present invention, the negative electrode current collector may be made of a material that does not cause chemical changes in the battery, is conductive, and does not react with lithium.

[0049] The negative electrode current collector may include at least one selected from the group consisting of copper (Cu), stainless steel (SS), titanium (Ti), iron (Fe), cobalt (Co), and nickel (Ni).

[0050] The negative electrode current collector may be in various forms, such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric having fine irregularities on the surface.

[0051] The positive electrode included in the all-solid-state battery according to one aspect of the present invention includes a positive electrode current collector and a positive electrode active material layer formed on one surface of the positive electrode current collector.

[0052] In one embodiment of the present invention, the positive electrode active material layer may include a positive electrode active material, a binder, and a conductive material.

[0053] In the present invention, the positive electrode active material is not particularly limited as long as it is a material capable of reversibly absorbing and releasing lithium ions. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), Li[Ni x Co y Mn z M v ]O2 (wherein M is any one or more elements selected from the group consisting of Al, Ga, and In; 0.3≦x<1.0, 0≦y, z≦0.5, 0≦v≦0.1, and x+y+z+v=1), Li (Li a M b-a-b’ M' b’ )O 2-c A c (wherein, 0≦a≦0.2, 0.6≦b≦1, 0≦b'≦0.2, 0≦c≦0.2; M includes Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn, and Ti; M' is at least one selected from the group consisting of Al, Mg, and B, and A is at least one selected from the group consisting of P, F, S, and N); 1+y Mn2-y Lithium manganese oxides such as LiMnO4 (where y is 0 to 0.33), LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-y Ni-site type lithium nickel oxide represented by MyO2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3); chemical formula LiMn 2-y M y Examples of the lithium manganese composite oxides include, but are not limited to, lithium manganese composite oxides represented by the formula LiMn2O2 (wherein M is Co, Ni, Fe, Cr, Zn, or Ta, and y is 0.01 to 0.1) or Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu, or Zn); LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion; disulfide compounds; and Fe2(MoO4)3.

[0054] The positive electrode active material may be included in an amount of 50 to 90 wt % based on the total weight of the positive electrode active material layer.

[0055] In an embodiment of the present invention, the type and content of the binder and conductive material included in the positive electrode active material layer may be the same as those used in the negative electrode active material layer.

[0056] In one embodiment of the present invention, the positive electrode current collector may be conductive without causing any chemical change in the battery.

[0057] The positive electrode current collector can be stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like. The positive electrode current collector can usually have a thickness of 3 to 500 μm, and fine irregularities can be formed on the collector surface to increase the adhesive strength of the positive electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0058] The solid electrolyte layer included in the all-solid-state battery according to one aspect of the present invention can include a sulfide-based solid electrolyte.

[0059] The sulfide-based solid electrolyte may contain sulfur (S) and have the ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table. Specifically, the sulfide-based solid electrolyte may be any one selected from the group consisting of Li6PS5Cl, Li2S-P2S5, Li2S-LiI-P2S5, Li2S-P2S5-LiCl, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2, and Li2S-GeS2-ZnS.

[0060] The average particle size (D50) of the sulfide-based solid electrolyte may be 100 nm to 700 nm, specifically, 100 nm or more, 200 nm or more, or 300 nm or more, and 1000 nm or less, 900 nm or less, 800 nm or less, or 700 nm or less. When the average particle size (D50) of the sulfide-based solid electrolyte is within the above range, lithium dendrites that may form at the negative electrode can be prevented from reaching the interface with the positive electrode, and short circuits can be prevented from occurring. The average particle size (D50) can be defined as a particle size that corresponds to 50% of the volume cumulative amount in a particle size distribution curve of the particles. The average particle size (D50) can be measured, for example, using a laser diffraction method. The laser diffraction method generally allows measurement of particle sizes from the submicron region to several mm, and can obtain results with high reproducibility and high resolution.

[0061] The solid electrolyte layer may also include a lithium salt.

[0062] The lithium salts include (CF3SO2)2NLi (Lithium bis(trifluoromethanesulphonyl)imide, LiTFSI), (FSO2)2NLi (Lithium bis(fluorosulfonyl)imide, LiFSI), LiNO3, LiOH, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN, and LiC(CF3SO2)3.

[0063] In addition, the lithium salt may be contained in an amount of 10 wt% to 30 wt% based on the total weight of the solid electrolyte, and specifically, the content of the lithium salt may be 10 wt% or more, 13 wt% or more, or 15 wt% or more, or 20 wt% or less, 25 wt% or less, or 30 wt% or less. If the content of the lithium salt is less than 10 wt%, the ion conductivity may be reduced, and if it exceeds 30 wt%, it may be impossible to form a solid electrolyte.

[0064] In the all-solid-state battery according to an embodiment of the present invention, a ratio of an initial charge capacity of the positive electrode active material layer to an initial charge capacity of the negative electrode active material layer may satisfy the following formula 1.

[0065] [Formula 1] 0 ≦ (b / a) < 0.01 In Equation 1, a is the initial charge capacity of the positive electrode active material layer determined from the first open circuit voltage to the maximum charge voltage (vs Li / Li+), and b is the charge capacity of the negative electrode active material layer determined from the second open circuit voltage to 0.01 V (vs Li / Li+).

[0066] The charge capacities a and b are determined by using an all-solid-state half-cell with a lithium counter electrode, and for the positive electrode, the charge capacities are determined by the first open circuit voltage to the maximum charge voltage (Vs. Li / Li + ), and for the negative electrode, 0.01 V (Vs. Li / Li + ) can be used to determine the

[0067] The maximum charging voltage of the positive electrode may be determined by the positive electrode active material. In one embodiment, the maximum charging voltage of the positive electrode active material is determined by the maximum voltage of a cell including a positive electrode active material that satisfies the safety conditions described in Appendix A of "Safety Requirements For Portable Sealed Secondary Cells, And For Batteries Made From Them, For Use In Portable Applications" by the Japanese Industrial Standards Committee, JISC8712:2015. The entire contents of JISC8712:2015 are incorporated herein by reference. According to one embodiment, the maximum charging voltage may be about 3 volts (V) to about 5V, about 3.5V to about 4.5V, or about 4V to about 4.4V, or about 4.1V to about 4.3V, or about 4.2V, or about 4.25V. In one embodiment, for example, when the positive electrode active material is lithium cobalt oxide (LCO), nickel cobalt aluminum (NCA), or nickel cobalt manganese (NCM), the maximum charging voltage is 4.1 V or 4.2 V (Vs. Li / Li + In one embodiment, for example, when the positive electrode active material is lithium cobalt oxide (LCO), NCA, or NCM, the maximum charging voltage is 4.25 V (Vs. Li / Li + ).

[0068] Manufacturing method for all-solid-state batteries The present invention also relates to a method for producing an all-solid-state battery, the method for producing the solid electrolyte comprising the following steps (1) to (7): (1) applying a slurry containing a negative electrode active material capable of alloying with lithium or forming a compound with lithium onto a negative electrode support and drying the slurry to form a negative electrode active material layer; (2) coating a slurry containing a positive electrode active material on a positive electrode current collector, drying the slurry, and then forming a positive electrode active material layer to manufacture a positive electrode; (3) disposing a solid electrolyte layer between the negative electrode active material layer and the positive electrode active material layer to form a laminate; (4) removing the negative electrode support from the laminate after pressing the laminate; (5) attaching a lithium thin film to one surface of the negative active material layer from which the negative support has been removed, and pre-lithiating the negative active material layer; (6) attaching a negative electrode current collector to the other side of the lithium thin film; and (7) Pressurizing the battery manufactured in step (6).

[0069] The types and contents of the materials used in the preparation method are the same as those described above.

[0070] Hereinafter, each step of the method for manufacturing an all-solid-state battery according to the present invention will be described in more detail.

[0071] In the present invention, in step (1), a slurry including a negative electrode active material that can be alloyed with lithium or that can form a compound with lithium is applied onto a negative electrode support and dried to form a negative electrode active material layer, thereby manufacturing a negative electrode.

[0072] Specifically, the slurry may be prepared by mixing the negative electrode active material, the solid electrolyte, the binder, and the conductive material in a solvent, and the concentration of the slurry may be appropriately adjusted so that the process of coating the negative electrode support can be smoothly performed.

[0073] The solvent is not particularly limited as long as it is a solvent that is commonly used for preparing a negative electrode slurry, and may be, for example, at least one selected from the group consisting of dimethylsulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, xylene, N,N-dimethylmethanamide (DMF), benzene, tetrahydrofuran (THF), and water.

[0074] In addition, the coating method is not particularly limited as long as it can coat the negative electrode slurry in a film form, and may be, for example, bar coating, roll coating, spin coating, slit coating, die coating, blade coating, comma coating, slot die coating, lip coating, or solution casting.

[0075] In addition, the negative electrode support is not particularly limited as long as it can function as a support on which the negative electrode slurry is applied, and may be, for example, a polyethylene terephthalate (PET) film, a polytetrafluoroethylene film, a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a vinyl chloride copolymer film, a polyurethane film, an ethylene-vinyl acetate film, an ethylene-propylene copolymer film, an ethylene-ethyl acrylate copolymer film, an ethylene-methyl acrylate copolymer film, or a polyimide film.

[0076] In the present invention, in the step (2), the slurry containing the positive electrode active material is coated on a positive electrode current collector and dried, and then a positive electrode active material layer is formed, thereby manufacturing a positive electrode.

[0077] The method of forming and applying the slurry to prepare the positive electrode may be the same as the method of forming the negative electrode active material layer in step (1).

[0078] In the present invention, in the step (3), a solid electrolyte layer may be disposed between the negative electrode active material layer and the positive electrode active material layer to form a laminate.

[0079] In the present invention, in the step (4), the laminate is pressed, and then the negative electrode support can be removed from the laminate.

[0080] The pressing may be isostatic pressing or uniaxial pressing under a pressure of 300 to 800 MPa and a temperature of 20 to 150° C. Specifically, the pressure during pressing may be 300 MPa or more, 400 MPa or more, or 450 MPa or more, and 600 MPa or less, 700 MPa or less, or 800 MPa or less. If the pressure is less than 300 MPa, interfacial contact between materials in the electrode and between the laminates may not be sufficiently formed, resulting in an excessive increase in interfacial resistance, and if it exceeds 800 MPa, the positive electrode active material may crack or break, resulting in a decrease in cell performance.

[0081] The temperature during the pressurization may be 20 to 150° C. Specifically, the temperature may be 20° C. or more, 40° C. or more, or 60° C. or more, and may be 100° C. or less, 120° C. or less, 140° C. or less, or 150° C. or less. If the temperature is less than 20° C., it may be difficult to form sufficient interfacial contact between materials in the electrode and between the laminates, and if the temperature exceeds 150° C., an unintended side reaction may occur at the interface between the solid electrolyte and the prelithiated negative electrode.

[0082] In the present invention, in the step (5), a lithium thin film may be attached to one side of the negative active material layer from which the negative support has been removed, thereby prelithiating the negative active material layer.

[0083] By attaching one surface of a lithium thin film to one surface of the negative electrode active material layer, lithium and / or lithium alloy contained in the lithium thin film is partially contained in the negative electrode active material layer, so that the negative electrode active material layer can be prelithiated.

[0084] In the present invention, in the step (6), a negative electrode current collector may be attached to the other surface of the lithium thin film to form a battery.

[0085] In the present invention, in the step (7), the battery is pressurized to produce an all-solid-state battery.

[0086] The pressurization of the battery may be performed by applying pressure and then aging.

[0087] The pressing may be isostatic pressing or uniaxial pressing at a pressure of 0.05 MPa to 100 MPa. Specifically, the pressure during pressing may be 0.05 MPa or more, 5 MPa or more, or 10 MPa or more, and may be 20 MPa or less, 30 MPa or less, 40 MPa or less, 50 MPa or less, 70 MPa or less, 90 MPa or less, or 100 MPa or less. If the pressure during pressing is less than 0.05 MPa, pre-lithiation may not be sufficiently performed, and the uniformity of the manufactured all-solid-state battery may decrease, and if it exceeds 100 MPa, the stacked form of the all-solid-state battery may be deformed due to the ductility of lithium.

[0088] The aging may be performed by storing at a temperature of 20° C. to 100° C. Specifically, the temperature during the aging may be 20° C. or higher, 30° C. or higher, or 40° C. or higher, and 80° C. or lower, 90° C. or lower, or 100° C. or lower. If the temperature during the aging is less than 20° C., pre-lithiation may not be sufficiently performed, and the uniformity of the manufactured all-solid-state battery may decrease, and if the temperature exceeds 100° C., an unintended side reaction may occur at the interface between the solid electrolyte and the pre-lithiated negative electrode.

[0089] Battery Module The present invention also provides a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.

[0090] Specific examples of the device include, but are not limited to, power tools that are driven by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.

[0091] Below, preferred examples are shown to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention. Naturally, such changes and modifications also fall within the scope of the appended claims.

[0092] Example 1 An all-solid-state battery was manufactured by the process shown in Figure 1.

[0093] (1) Anode (10) Manufacturing A negative electrode active material was prepared by mixing amorphous carbon black and silver (Ag) in a weight ratio of 1:3.

[0094] Styrene butadiene rubber (SBR) was prepared as a binder.

[0095] The negative active material and the binder were mixed in a weight ratio of 95:5 and then added to an NMP (N-Methyl-2-Pyrrolidone) solvent to prepare a slurry. The negative active material and the binder were added until the viscosity of the slurry became suitable for film formation using a blade coater.

[0096] The slurry was applied onto a polyethylene terephthalate (PET) film serving as a negative electrode support using a blade coater and dried to form a negative electrode active material layer on one surface of the negative electrode support.

[0097] (2) Positive electrode (20) Manufacturing LiNi as the positive electrode active material 0.8 Co 0.15 Mn 0.05 O2 (NCM), carbon nanofiber (CNF) as a conductive material, and styrene-butadiene rubber (SBR) as a binder were prepared.

[0098] The positive electrode active material, conductive material, and binder were mixed in a weight ratio of 85:5:10, and then added to an NMP (N-Methyl-2-Pyrrolidone) solvent to prepare a slurry.

[0099] The slurry was applied to one side of a positive electrode current collector using a blade coater and dried to prepare a positive electrode having a positive electrode active material layer formed on one side of the positive electrode current collector. At this time, an Al foil having a thickness of 10 μm was used as the positive electrode current collector.

[0100] (3) Laminate formation A solid electrolyte layer was disposed between the negative electrode active material layer and the positive electrode active material layer to form a laminate. At this time, a Li6PS5Cl solid electrolyte layer (30) was used as the solid electrolyte layer.

[0101] (4) Pressing the laminate and removing the negative electrode support The laminate was isostatically pressed at a temperature of 80° C. and a pressure of 500 MPa, and then the negative electrode support was removed.

[0102] (5) Pre-lithiation In the laminate, one surface of a lithium thin film (Li foil) was attached to one surface of the negative electrode active material layer that had been in contact with the negative electrode support, and the negative electrode active material layer was prelithiated.

[0103] (6)Battery manufacturing A negative electrode current collector was attached to the other side of the lithium thin film to manufacture an all-solid-state battery 100. At this time, a stainless steel foil having a thickness of 10 μm was used as the negative electrode current collector.

[0104] (7) Battery pressure and aging The fabricated battery was uniaxially pressed at 10 MPa and aged at 60° C. for 24 hours.

[0105] Comparative Example 1 An all-solid-state battery was manufactured in the same manner as in Example 1, except that a negative electrode that had not been pre-lithiated was used and no pressing or aging process was performed after the battery was manufactured.

[0106] Experimental example 1: Evaluation of physical properties of all-solid-state batteries An experiment was carried out to measure the initial discharge capacity of each of the all-solid-state batteries produced in Example 1 and Comparative Example 1.

[0107] For each solid-state battery, 0.1C (0.55mA cm -2 ) Charging / 0.1C (0.55mA cm -2 ) discharge conditions and the experimental results were measured.

[0108] FIG. 2 is a graph showing the initial charge / discharge profiles of the all-solid-state batteries produced in Example 1 and Comparative Example 1, respectively.

[0109] 2, the discharge capacity of Example 1 was 206 mAh / g, and the discharge capacity of Comparative Example 1 was 198 mAh / g. Thus, it can be seen that Example 1 had an increased discharge capacity compared to Comparative Example 1.

[0110] Although the present invention has been described above using limited examples and drawings, the present invention is not limited thereto, and it is of course possible for a person having ordinary knowledge in the technical field to which the present invention pertains to make various modifications and variations within the technical spirit of the present invention and the equivalent scope of the claims described below. [Explanation of symbols]

[0111] 10: Negative electrode 20: Positive electrode 30: Solid electrolyte layer 100: All-solid-state battery

Claims

1. In an all-solid-state battery including a positive electrode, a negative electrode, and a solid electrolyte layer, The positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on one surface of the positive electrode current collector, the negative electrode includes a negative electrode current collector, a lithium metal layer formed on one surface of the negative electrode current collector, and a negative electrode active material layer formed on one surface of the lithium metal layer, the solid electrolyte layer is disposed between the positive electrode active material layer and the negative electrode active material layer, The negative electrode active material layer comprises a negative electrode active material capable of being alloyed with lithium or capable of forming a compound with lithium, and lithium.

2. 2. The all-solid-state battery according to claim 1, wherein the concentration of the lithium in the negative electrode active material layer has a concentration gradient that gradually decreases from one surface in contact with the lithium metal layer to the other surface.

3. 2. The all-solid-state battery according to claim 1, wherein the lithium contained in the negative electrode active material layer is diffused in the form of lithium ions or exists in a form bonded to the negative electrode active material.

4. 2. The all-solid-state battery according to claim 1, wherein the negative electrode active material includes at least one selected from the group consisting of amorphous carbon, gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn).

5. 2. The all-solid-state battery according to claim 1, wherein the negative electrode active material layer has a thickness of 5 μm or more and 200 μm or less.

6. The all-solid-state battery according to any one of claims 1 to 5, wherein a ratio of an initial charge capacity of the positive electrode active material layer to an initial charge capacity of the negative electrode active material layer satisfies the following formula 1: [Formula 1] 0≦(b / a)<0.01 Here, a is the difference between the first open circuit voltage and the maximum charging voltage (vs Li / Li + ) is the initial charge capacity of the positive electrode active material layer determined up to b is the charge capacity of the negative electrode active material layer determined from the second open circuit voltage to 0.01 V (vs Li / Li+).

7. (1) applying a slurry containing a negative electrode active material capable of alloying with lithium or forming a compound with lithium onto a negative electrode support and drying the slurry to form a negative electrode active material layer; (2) coating a slurry containing a positive electrode active material on a positive electrode current collector, drying the slurry, and forming a positive electrode active material layer thereon to manufacture a positive electrode; (3) disposing a solid electrolyte layer between the negative electrode active material layer and the positive electrode active material layer to form a laminate; (4) removing the negative electrode support from the stack after pressing the stack; (5) attaching a lithium thin film to the surface of the negative active material layer from which the negative support has been removed, and pre-lithiating the negative active material layer; (6) attaching a negative electrode current collector to the other side of the lithium thin film; and (7) A method for manufacturing an all-solid-state battery, comprising: (a) pressurizing the battery manufactured in the step (6).

8. 8. The method of claim 7, wherein the pressing in step (4) is performed by isostatic pressing or uniaxial pressing at a pressure of 300 MPa to 800 MPa and a temperature of 20° C. to 150° C.

9. The method for manufacturing an all-solid-state battery according to claim 7 or 8, wherein the pressurization in step (7) is followed by aging.

10. The method for producing an all-solid-state battery according to claim 9 , wherein the pressing is isostatic pressing or uniaxial pressing at a pressure of 0.05 MPa or more and 100 MPa or less.

11. The method for producing an all-solid-state battery according to claim 9 , wherein the aging is performed by storing the battery at a temperature of 20° C. or higher and 100° C. or lower.

Citation Information

Patent Citations

  • Negative electrode for secondary battery and secondary battery using the same

    JP2003217574A

  • Method of manufacturing lithium ion secondary battery

    JP2011249046A

  • Negative electrode for lithium ion secondary battery

    JP2012009209A

  • Anode material for all-solid-state secondary battery, anode layer including the same, all-solid-state secondary battery, and manufacturing method for the same

    JP2022098487A

  • Secondary battery manufacturing method

    JP2022533496A